Exploring the Properties and Potential Uses of Biocarbon from Spent Coffee Grounds: A Comparative Look at Dry and Wet Processing Methods - Yang, Jie; Zhao, Zeyuan; Hu, Yulin; Abbey, Lord; Cesarino, Ivana [UNESP]; Goonetilleke, Ashantha; He, Quan (MDPI, 2023)
Coffee is among the most widely consumed beverages worldwide, leading to the annual generation of substantial quantities of spent coffee grounds (SCGs). This study explored the influence of fabrication methods on the properties and potential applications of the resulting biocarbon materials. Dry methods (torrefaction at 270 °C and slow pyrolysis at 500 °C) and wet methods (hydrothermal carbonization HTC at 210 °C and hydrothermal liquefaction HTL at 270 °C) were employed to fabricate SCG-based biochar and hydrochar, respectively. The carbonization degree followed the order of slow pyrolysis > HTL > HTC ≈ torrefaction, yielding significant differences in energy properties, elemental composition, morphology, and surface functionality. Slow pyrolysis biochar was suitable for energy applications due to a similar fuel ratio as and higher heating value than semianthracite coal. For agricultural applications, SCG biochar produced through dry methods could be utilized to mitigate acidic soil conditions, whereas HTC hydrochar, with its elevated surface area and porosity, could enhance soil microbiological diversity and water-holding capacity, as well as benefit environmental applications such as wastewater remediation. In summary, the findings of this study are anticipated to inform decision-making processes concerning sustainable waste management of SCGs and the exploration of carbon-based materials applications across diverse sectors.
Keywords: biocarbon materials; physicochemical properties; potential applications; thermochemical carbonization; waste management